Surgical and Behavioral Relationships With Welfare - Bain, Melissa (Frontiers in Veterinary Science, 2020)
Veterinarians perform surgery for a number of reasons, from treating a problem to preventing future problems. There is an inextricable link between the physical and psychological aspects of an animal’s health, and surgery is often a conduit to bridge that gap. Some surgical procedures can affect an animal’s behavior, such as castration, and some pose an ethical dilemma, such as ear cropping and declawing. Ameliorating pain, decreasing stressful experiences for the animal, and identifying and treating concurrent problem behaviors are hallmarks of improving animal welfare. The purpose of this article is to outline some of these interrelationships and ethical dilemmas, providing evidence-based verification as applicable.